Pengaruh Keterlibatan Kerja dan Kompensasi Kerja Terhadap Kinerja Karyawan Pada CV Puspasari Collection Gianyar - Deswanta, I Putu Yoga Ardi; Hartati, Putu Sri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to understand the results of CV Puspasari Collection Gianyar's loyalty work commitment and employee compensation. There are 71 people in the population and sample. The sample collection method used is the saturated sample method. Data collection is carried out through a series of questions, which have been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis. According to the analysis results, it is found that work input has a positive and significant impact on employee performance. Work compensation has a positive and significant impact on employee performance. Then, work and salary work are actively involved at the same time, and significantly affect the performance of the employee resume Puspasari Collection Gianyar. It can be proved that Ftabel = 3.13 <Fhitung = 41.020, the signal value is 0.000 <0.05.